“Move or Not to Move”—Red Deer Stags Movement Activity during the Rut - Erika Csányi; Tamás Tari; Sándor Németh; Gyula Sándor (Animals, 2022)
Detailed animal movement analysis can help understand spatial population processes as the ultimate consequences of individual behaviour and ecological impacts. The mating strategy of mammalian herbivores is adapted to the distribution of females; thus, it is important to observe the activity of animals during a rut. In this paper, we used a new approach to examine the relationship between red deer stags’ movement activity and the fertile period of hinds. We presumed a relationship between stags’ daily activity changes and the period when hinds are in heat. We determined temporal conception trends, including the first and last conception dates in the examined population and the conception peak. In the same period, i.e., in the interval of major ecological significance when mating takes place, the activity of stags was analysed by GPS telemetry. The data collected in the examined period indicate that 60% of the hinds were conceived between 31 August and 19 September. We demonstrated that conception rates differed significantly between the first and second half of the rutting period. At the beginning of the reproductive cycle, the high number of hinds on heat (oestrus synchrony) increased the activity of stags (harem herding) compared to the pre-rutting period. As the mating season progressed, the movement activity of stags increased more (searching behaviour), induced by the decreasing number of fertile hinds. Therefore, we found that the oestrus of hinds significantly influenced the movement activity of stags in red deer.